1986
DOI: 10.1051/jphyscol:19868155
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS-STUDY OF THE Zn2+ COORDINATION IN AQUEOUS HALIDE SOLUTIONS

Abstract: Aqueous solutions of ZnCl2, ZnBr2 and ZnI2 in the concentration range from 0.1 molal up to saturation have been studied by EXAFS experiments at the zinc K-edge. EXAFS spectra of the crystalline compounds of ZnCl2, ZnBr2, ZnI2 and ZnSO4*7H2O have been used as references. I n the low concentration range up to 0.5 molal a complete hydration of the zinc ions by 6 - 7 water molecules is observed. At high concentrations above 5 molal the mean local coordination around the zinc ions consists of halide ions and water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…X-ray diffraction and EXAFS (extended X-ray absorption fine structure spectroscopy) have provided invaluable direct information by probing the first shell about the cation. Several studies have convincingly concluded the absence of chloride ions in the first coordination sphere of the nickel ion. , , Other works have provided information about the presence, or absence, of Cl – ions in the first shell of most cations considered in this work, including Mn­(II), Co­(II), , Cu­(II), ,, Zn­(II), and Cd­(II) …”
Section: Experimental Informationmentioning
confidence: 57%
See 1 more Smart Citation
“…X-ray diffraction and EXAFS (extended X-ray absorption fine structure spectroscopy) have provided invaluable direct information by probing the first shell about the cation. Several studies have convincingly concluded the absence of chloride ions in the first coordination sphere of the nickel ion. , , Other works have provided information about the presence, or absence, of Cl – ions in the first shell of most cations considered in this work, including Mn­(II), Co­(II), , Cu­(II), ,, Zn­(II), and Cd­(II) …”
Section: Experimental Informationmentioning
confidence: 57%
“…including Mn(II), 46 Co(II), 45,47 Cu(II), 34,45,48 Zn(II), 49 and Cd(II). 40 By denoting by p n the proportion of a complex of stoichiometry n for a complex MCl n , the mean coordination number of the metal cation with chlorides may be defined as,…”
Section: Speciation and Mean Coordination Number Of The Metal Cationmentioning
confidence: 99%
“…A number of experimental studies have been devoted in the past to the structural characterization of aqueous and non-aqueous ZnCl 2 solutions. [36][37][38][39][40][41][42][43][44] Kruh and Standley 37 performed x-ray diffraction on aqueous solutions of ZnCl 2 with concentration ranging from 5 to 27.5 m. In the higher concentration range they found an average of three chloride ligands around each zinc along with one water forming a tetrahedral arrangement. These results were confirmed using Raman, x-ray, and neutron diffraction experiments.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 These advantages make XAS an excellent tool for investigating the structures of organozinc reagents in solution. [19][20][21][22][23][24] Zinc iodide adopts a tetrahedral coordination geometry which gives a sharp edge jump originating from the 1s to 4p electron transition in the X-ray absorption near-edge structure (XANES) spectrum. 25 As shown in Fig.…”
mentioning
confidence: 99%